Integrating Sustainable Development Goals in Physical and Mental Health Education: A Study on the 8th Grade Fiqh Textbook - Ahmadi Martha Habibi; Chusniatun; Mahasri Shobahiya; Fahmi Ulum Al Mubarok; Lutfi Zaki Al Manfaluthi (Universitas Muhammadiyah Surakarta, 2024)
Objective: This study aims to analyze the content of Fiqh textbooks used in Muhammadiyah educational institutions, especially to assess the extent to which the material is in line with the ISMUBA curriculum and its relevance to the Sustainable Development Goals (SDGs). Theoretical framework: Based on Islamic education that is integrated with global development goals, especially the values of justice, social responsibility, and environmental conservation. Literature review: Reviewing the Islamic education curriculum of Muhammadiyah, the suitability of textbooks with the curriculum, and the relationship between religious education and global issues in the context of the SDGs. Methods: Using content analysis of Fiqh textbooks from the Dikdasmen Council and the Muhammadiyah Islamic Boarding School Development Institute, with a focus on the structure, content, and relationship with the SDGs. Results: The results of the study show that the Fiqh textbook published by the Muhammadiyah Higher Education Council is by the ISMUBA curriculum, while the version from the Islamic Boarding School Development Institute is still relevant, even though the structure is different. The material covers the pillars of Islam and supports the SDGs: fasting and prayer (Goal 3), zakat and social (Goals 1 & 10), and environmental ethics (Goal 13). Implications: Shows that Islamic education can contribute to the formation of a religious, social, and environmentally caring generation that is ready to face global challenges. Novelty: Offering a new perspective by connecting the Muhammadiyah Fiqh textbook with the SDGs, expanding the function of religious education towards sustainable development.